Wykonaj działania a następnie oblicz wartość liczbową wyrażenia:

a) (2x + 2y) - (x + y) + (x-2y) dla x=0,5 i y= -1

b) (2a -3b) - (-5a+4b) dla a= 1/7 (jedna siodma) i b= -2

c) (2x ² - 4y) - (9x² + 6y) + (2x² + y) dla x=0,2 i y= - 1/3 (jedna trzecia

d) 5a-[3a² + 4a - (-3a + 4a)] dla a= - 1/2 (jedna druga)

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-25T23:36:11+01:00
A)
(2x + 2y) - (x + y) + (x-2y) =2x+2y-x-y+x-2y=2x-y= 2*0,5 - (-1)=1+1=2


b)
(2a -3b) - (-5a+4b) =2a-3b+5a-4b=7a-7b=7*1/7-7*(-2)= 1+14=15


c)
(2x ² - 4y) - (9x² + 6y) + (2x² + y) =2x ² - 4y - 9x² - 6y + 2x² + y=

- 5x² -9y=- 5*(0,2)² -9*(-1/3)=5*0,04+3=0,2+3=3,2

d)
5a-[3a² + 4a - (-3a + 4a)]= 5a-[3a² + 4a +3a -4a]= 5a-3a² - 4a -3a +4a=
- 3a² +2a= -3*(-1/2)² + 2*(-1/2)= -3*(-1/8)-1=+3/8 -1= -5/8

































































1 5 1
2010-03-25T23:42:44+01:00
A)
(2x + 2y) - (x + y) + (x-2y) dla x=0,5 i y= -1
2x+2y-x-y+x-2y=2x-y=2*0,5-(-1)=1+1=2

b)
(2a -3b) - (-5a+4b) dla a= 1/7 (jedna siodma) i b= -2
2a-3b+5a-4b=7a-7b=7*1/7-7*(-2)=7/1*1/7+14=7/7+14=1+14=15
c)
(2x ² - 4y) - (9x² + 6y) + (2x² + y) dla x=0,2 i y= - 1/3 (jedna trzecia
2x² -4y-9x²-6y+2x²+y=-5x²-9y=-5*(0,2)²-9*1/3=-5*0,04-9/3=
=-0,2-3=-3,2
d)
5a-[3a² + 4a - (-3a + 4a)] dla a= - 1/2 (jedna druga)
5a-[3a²+4a+3a-4a]=5a-3a²-4a-3a+4a=2a-3a²=2*0,5+3*(0,5)²=
=1+3*0,25=1+0,75=1,75